PROFESSIONALISM OF LECTURERSTO IMPROVE CHARACTER OF THE STUDENT TEACHERS OF THE MILLENNIAL ERA DISRUPSI - Yudha, Chrisnaji Banindra (Universitas Sebelas Maret, 2018)
Professionalism of lecturers in the form kartakter when it becomes very important for implanted. The lecturer was cast in gold generation nation Indonesia and relay the leadership of the nation and the State. The professionalism of the lecturer continually formed and conditioned on environment of the College and the community. Literacy innovation in science and technology are becoming a must-have capability of professional lecturers, given the current has entered the digital age. Professionalism lecturer always should be improved and developed in order to face the challenges of global human resources and setting up a reliable, resilient, and character.